Advanced models for the construction of an NbS catalogue for resilience and biodiversity - Roberto Bologna; Giulio Hasanaj (Agathón)
The article illustrates the results of a survey undertaken by the authors within the research activities of the National Biodiversity Center established according to the PNRR objectives, regarding the main cataloguing platforms of Nature-based Solutions (NbS) for urban biodiversity aimed at restoring natural resources, creating resilient ecosystems, and promoting ecosystem benefits in cities. The analysis and comparison of case study catalogue models focused on NbS has led to the development of an organisational structure of metadata for their cataloguing, to be adopted in the Mediterranean context for the processes of urban forestation, nature-based regeneration, and improvement of ecological connectivity between urban, peri-urban, and rural areas.